A comparison study on the use of knowledge management systems and enterprise microblogging systems for organizational knowledge sharing - Lee, Angela Siew Hoong *; Lim, Tong Ming *; Rasimah Aripin,; Lim, Justin Renn Aun (2012)
Knowledge Management System (KMS) has been widely used by many knowledge-centric organizations to manage their organizational knowledge activities and to improve knowledge sharing among employees. However, it is essential to study the utilization rate of the system in the company. In this research, the KMS and two different enterprise microblogging systems are studied to determine which systems is able to facilitate better knowledge sharing within a company. We studied these systems’ background information, features and functionalities to compare and contrast their benefits and usefulness toward the organizational knowledge management needs. Detailed documents examination and interview with the employees were conducted to collect data to analyze the rate of KMS utilization, benefits and usefulness. Two microblogging systems were introduced to the employees and their attractive features and benefits offered by the microblogging platforms were presented to the employees in order to study and determine their usefulness and rate of utilization in the company. The data collected was analyzed and a comparison table was created which described the similarities and differences in term of features and functions of all three systems. In this research, it was found that the enterprise microblogging systems offer attention-grabbing features and functions which are identical to other social networking systems like Facebook and Twitter had effectively improved the rate of utilization and hence increases the knowledge sharing in the companies. The research outcome had shown that enterprise microblogging systems have the potential to improve knowledge sharing activity within a company compared to a KMS.